Kualitas Pelayanan Bagi Pasien Tuberkulosis terhadap Kepatuhan Minum Obat di Puskesmas Se-Kabupaten Sijunjung Tahun 2025 - Dian Fadhlina; Sumihardi, Sumihardi (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
Tuberculosis (TB) remains a global and national health issue. Sijunjung Regency has seen an increase in TB cases, with fluctuating treatment success rates. Medication adherence is a key factor in treatment success and is influenced by the quality of health care services. This study aims to analyze the quality of services regarding medication adherence among TB patients, explore patients’ perceptions, describe service factors influencing adherence, and understand the role of health workers from the patients’ perspective at Community Health Centers (Puskesmas) throughout Sijunjung District. This study employed a qualitative approach with a phenomenological design. The primary informants consisted of 8 TB patients, plus key informants (2 healthcare workers) and additional informants (2 family members). Data were collected through in-depth interviews, observations, and document reviews. Analysis utilized the Miles & Huberman model.Research results on the quality of healthcare services are related to the level of medication adherence in tuberculosis patients. The dimensions that contribute most to adherence are empathy, assurance, and responsiveness. Positive perceptions are seen in aspects of interpersonal relationships (friendliness, patience, effective communication) and logistical reliability (drug availability), while negative perceptions are related to the lack of privacy in waiting rooms, long administrative waiting times, and inflexible service hours for informal workers. Health service factors that influence adherence include continuous education and information, active supervision and monitoring, ease of service access, and support from healthcare workers. The role of healthcare workers in supporting patient adherence, according to the patient's perspective, is as educators and motivators.Based on this study, high-quality care particularly empathy, assurance, and responsiveness is crucial for patient adherence. Improvements to physical facilities and greater flexibility in service hours are needed.